CENTRE AND PERIPHERY IN BAVARIA? POLARIZATION TENDENCY IN A GROWING GERMANY REGION - Scheffer, Jörg (2008)
The equality of living conditions is one of the most important aims of regional planning in Germany. Politicians tend to describe significant structural differences between the so-called “centres” and the “peripheries” in rather broad terms, especially when referring to Eastern and Western Germany. However, in individual successful federal states which are themselves perceived as centres, such as Bavaria, regional disparities seem largely overcome. Yet, a closer analysis of the structures prevalent in Bavaria reveals the existence of considerable divergences in economy and the distribution of population in this federal state, too. These disparities will become sharper in the future. Despite Bavaria’s general economic power, only a limited equality can be achieved through instruments of regional development.